Molecular Docking and In Silico Evaluation of Beluntas (Pluchea indica) Phytochemicals as Potential Angiotensin-Converting Enzyme Inhibitors for Hypertension Treatment - Achmad Ramadhanna’il Rasjava; Nabila Hadiah Akbar; Aulia Rhamdani Arfan; Dyah Ayu Pramoda Wardani; Aditya Maulana Perdana Putra; Khoirunnisa Muslimawati; Putri Helena Junjung Buih; Taufik Muhammad Fakih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Hypertension remains a major global health concern due to its high prevalence and strong association with cardiovascular diseases and kidney failure. A key component of blood pressure regulation is the Angiotensin-Converting Enzyme (ACE), which catalyzes the conversion of Angiotensin I into the vasoconstrictor Angiotensin II, making it a primary target for antihypertensive drugs. Although synthetic ACE inhibitors such as ramiprilat are effective, their use is often associated with adverse effects, highlighting the need for safer alternatives. This study employs molecular docking and in silico analysis to evaluate the potential of phytochemicals from beluntas (Pluchea indica) as natural ACE inhibitors. A total of 110 phytoconstituents were screened for pharmacokinetic properties using ADMET analysis, leading to the selection of 20 ligands for docking simulations. Among these, 4,5-di-O-caffeoylquinic acid exhibited the highest binding affinity (-9.409 kcal/mol), followed by di-O-caffeoylquinic acid (-8.984 kcal/mol) and quercetin-3-O-β-D-galactopyranoside (-8.372 kcal/mol). These compounds demonstrated stronger binding affinities than the ACE natural substrate, Angiotensin I (-7.133 kcal/mol), and the ACE inhibitor, ramiprilat (-8.717 kcal/mol), suggesting their potential as competitive ACE inhibitors. The binding interactions of these compounds were characterized by hydrogen bonding with key catalytic residues (HIS368, GLU368), electrostatic stabilization, and hydrophobic interactions within the enzyme active site. Notably, caffeoylquinic acid derivatives closely mimicked the binding mode of ramiprilat, whereas quercetin glycosides exhibited a distinct interaction pattern, indicating a possible alternative inhibitory mechanism. These findings provide evidence supporting the potential of P. indica phytochemicals as natural ACE inhibitors and warrant further investigation into their therapeutic applications in hypertension management.